Stingless bees of Costa Rica - Aguilar Monge, Ingrid (2012)
The keeping of stingless bees (Apidae, Meliponini) or meliponiculture is carried out in a rustic and traditional way in Costa Rica. This is an activity present in several regions of the country, especially among the inhabitants of rural areas, mostly on the Pacific coast rather than the Atlantic region. According to our most recent data, the number of stingless bee keepers has progressively increased. However, compared to previous studies, the number of colonies per person has declined. This partially is due to the practice, in many cases, of keeping bees as a hobby more than as a source of improvement in family income. A total of 20 different domesticated species have been reported and the most commonly kept species is T. angustula.